Studies of Functionalized Polyurethanes for Blood Contacting Applications - Vanderkamp, Nick (My University, 1988)
The synthesis of novel polyurethanes for use in blood contacting applications was investigated. A series of polyurethanes containing biologically active groups in the hard segment was synthesized. Sulphonate-containing polyurethanes were produced using a sulphonated chain extender (biphenyl diamino disulphonic acid) and these polymers were subsequently reacted to incorporate arginine methyl ester groups via sulphonamide bonds. The novel polyurethanes were initially evaluated using elemental sulphur analysis and nitrogen analysis, gel permeation chromatography and Fourier transform infrared spectroscopy to verify reaction of the sulphonated chain extender and addition of arginine methyl ester. Three sulphonated polyurethanes covering a range of sulphonate content were produced by varying the prepolymer and hard segment lengths. These three polymers and the three corresponding arginine methyl ester containing polymers were characterized to relate both bulk and surface structure to physical and biological properties. Elemental analysis, gel permeation chromatography and Fourier transform infrared spectroscopy were used to characterize the molecular structure. These techniques provided results consistent with the expected reaction mechanisms. Electron spectroscopy for chemical analysis and contact angle measurements were used to analyse the surface structure. Preliminary contact angle data indicate that the sulphonated polyurethane surfaces are hydrophilic, but further investigation is required before a firm conclusion can be reached. ESCA results indicate that while soft segment surface enrichment is taking place there are significant numbers of sulphonate groups present at the polyurethane surface. Mechanically these polymers have similar ultimate tensile strength but lower elongation than polyurethanes produced using aliphatic diamines, like ethylene diamine. This is probably due to increased microphase segregation arising partly from incompatibility of the aromatic chain extender with the aliphatic soft segment and possibly partly to ion cluster formation. The incorporation of arginine methyl ester groups increases both the elongation and the tensile strength, probably due to reduced phase segregation. Fibrinogen adsorption experiments in plasma were conducted to evaluate the blood response of these polymers. The plasma adsorption "isotherms" for the novel polyurethanes do not show transient fibrinogen adsorption (Vroman effect) which has been observed on a number of other surfaces including a wide range of polyurethanes. Instead, the initially adsorbed fibrinogen remains adsorbed. Also the levels of fibrinogen adsorption from plasma are three to four times greater than observed on previously studied surfaces. Conversion of some of the sulphonate groups to sulphonamide-bonded arginine methyl ester restores the Vroman effect and results in lower levels of retained fibrinogen. These data suggest the possibility of a specific interaction between sulphonate groups and fibrinogen.
Functionalized Polyurethanes for Blood Contacting Applications
Keywords: polyurethane; blood; application; functional